Effects of sphingoid bases on the sphingolipidome in early keratinocyte differentiation. (23rd September 2013) - Sigruener, Alexander; Tarabin, Victoria; Paragh, György; Liebisch, Gerhard; Koehler, Tim; Farwick, Mike; Schmitz, Gerd
Abstract Keratinocyte sphingolipids are structural elements of epidermal permeability barrier and potential regulators of epidermal functions. We tested the influence of sphingoid bases sphinganine, sphingosine and phytosphingosine on in vitro keratinocyte differentiation. Lipidomic and transcriptomic analysis after treatment emphasizes sphinganine and phytosphingosine as potent modulators of keratinocyte differentiation and lipid metabolism. Sphinganine treatment regulated differentiation and sphingolipid metabolism‐related genes, and also increased all major ceramide species. Sphingosine treatment increased ceramide and phytoceramide pools without changes in dihydroceramides. Phytosphingosine treatment markedly increased phytoceramide pools without raising ceramide or dihydroceramide levels. Sphinganine treatment increased specifically very long chain ceramides essential for intact barrier function. In summary, sphingoid bases, especially sphinganine, promote differentiation and ceramide production in keratinocytes. Free sphinganine may serve as a dermatological and cosmetic agent by enhancing formation and maintenance of an intact epidermal lipid barrier, with beneficial effects for skin and hair care applications.